The effects of Using Nano-Meniran (Phyllanthus niruri) Extract on the Feed Economic Value and Income Over Feed Costs of Broiler Chicken Farm - Elita Triwijayanti Aqfari; Emy Koestanti Sabdoningrum; Sri Hidanah; Widya Paramita Lokapirnasari; Soeharsono Soeharsono; Wiwik Misaco Yuniarti (Faculty of Animal Science, Universitas Brawijaya, 2023)
This study aims to determined the effects of using nano-meniran (Phyllanthus niruri) extract on the feed economic value and income over feed costs of broiler chicken farms. This research method was an observational study with a sample of one-day-old Cobb strain broiler chicken at PT. Haraka Kitri Endah. A total of 79.600 day-old-chicken were divided into 4 groups of treatments and eight replications, each group of treatments consisted of 19.900 day-old-chicken. Treatments are given for 14 days – from the chickens are 21 days old until the chickens reach 35 days old consisted of T0, as the control group, was not given nano-meniran extract and was only given mineral feed; T1 was given nano-meniran extract 5%; T2 was given nano-meniran extract 10%; and T3 was given nano-meniran extract 20%. The administration of nano-meniran (Phyllanthus niruri) extract on the feed’s economic value and income over feed costs showed a significant difference (p<0.05). Research results showed the feed economic value of the broiler chickens are T0 = IDR 13.345,21; T1= IDR 12.315,57; T2 = IDR 13.057,11; and T3 = IDR 13.476,69. Income over feed costs calculations showed that T0 = IDR 8.942,13; T1= IDR 11.276,63; T2 = IDR 8.848,44; and T3 = IDR 8.299,44. T1 with nano-meniran extract 5% gives the best result. This research showed that nano-meniran extract has an immunomodulatory activity that positively impacts broiler chickens because it reduces the feed’s economic value and increases the income over feed costs.